2022
DOI: 10.1002/adts.202100563
|View full text |Cite
|
Sign up to set email alerts
|

The Transient Response of Organic Electrochemical Transistors

Abstract: A fast response of organic electrochemical transistors (OECTs) to electrical or chemical changes is essential for a widespread acceptance of this technology. However, finding design rules for fast switching OECTs is complicated by the fact that current transient device models are highly simplified and rely on a 1D approximation of the device that neglects details of the ion and hole concentration inside the transistor channel. To improve the understanding of transient processes limiting the speed of OECTs, a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…The spin-coated device performs better than the electropolymerized ones in terms of the frequency response; therefore, a temporal response of six identical devices was captured as well, yielding averaged time constants of τ OFF = (36.4 ± 1.8) μs and τ ON = (124.0 ± 1.9) μs for devices with W = 50 μm and d = 400 nm (Figure C). The time constant for turning ON the transistor is significantly slower, showing the same behavior as reported in some other works. Paudel et al showed that for a planar OECT, lateral current in the channel when switching the transistor off is the limiting factor, as the channel length is usually much larger than the thickness of the semiconductor, rendering turning OFF the slower process of the two. Here, we attribute the opposite behavior partly to the fact that the channel length and semiconductor thickness are similar.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The spin-coated device performs better than the electropolymerized ones in terms of the frequency response; therefore, a temporal response of six identical devices was captured as well, yielding averaged time constants of τ OFF = (36.4 ± 1.8) μs and τ ON = (124.0 ± 1.9) μs for devices with W = 50 μm and d = 400 nm (Figure C). The time constant for turning ON the transistor is significantly slower, showing the same behavior as reported in some other works. Paudel et al showed that for a planar OECT, lateral current in the channel when switching the transistor off is the limiting factor, as the channel length is usually much larger than the thickness of the semiconductor, rendering turning OFF the slower process of the two. Here, we attribute the opposite behavior partly to the fact that the channel length and semiconductor thickness are similar.…”
Section: Resultssupporting
confidence: 71%
“…The time constant for turning ON the transistor is significantly slower, showing the same behavior as reported in some other works. 27−30 Paudel et al 27 showed that for a planar OECT, lateral current in the channel when switching the transistor off is the limiting factor, as the channel length is usually much larger than the thickness of the semiconductor, rendering turning OFF the slower process of the two. Here, we attribute the opposite behavior partly to the fact that the channel length and semiconductor thickness are similar.…”
Section: Resultsmentioning
confidence: 99%
“…Results observed in Figure S8 show that the nature of the charge of the polyelectrolyte does not affect the shape of the transient behavior of the devices; that is, there is no effect ascribed to the charge exclusion, showing that the process is governed by the exchange of both type of ions. Moreover, it is important to note that, compared to other recently reported OECTs, the obtained t average of 41 μs (for 1:5 dilution OECTs) is remarkably lower. A detailed comparison with previously reported OECTs is presented in Table S1.…”
Section: Resultsmentioning
confidence: 53%
“…OECTs generally exhibit a response time of up to a few tens of microseconds. 60,65 OECTs with gel-or solid-state electrolytes show even slower t. This range of response time resembles the electrophysiological signal, establishing OECTs as the most suitable for synaptic application. 66 Another performance parameter for OECTs is the effective formation of EDL and electrochemical ion doping in the channel, leading to G m increment.…”
Section: Low-voltage Operating Mechanism Of Oectmentioning
confidence: 90%